Algorithm for Hydraulic and Thermal Calculation of a Two-Pipe Heating Network Based on Quasi-One-Dimensional Modeling (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Algorithms for hydraulic and thermal calculation of a two-pipe heating network with a limited number of heat exchangers have been developed. When modeling the functioning of the network, a single-term representation of the resistance coefficient, analogues of Kirchhoff’s laws taking into account the variability of the leveling height of the network route, as well as Shukhov’s formula and the average flow temperature of the coolant at the confluence of flows were used. Formulas were obtained for determining arc flow rates, nodal pressure and temperature, taking into account the characteristics of individual heat exchangers. Based on the proposed calculation method, a software product was compiled and a computational experiment was carried out within the framework of the quadratic resistance law. Summary calculation results related to the network and individual heat exchangers are presented. The pressure and heat losses determined during the calculation make it possible to select the power of the heat source and pump.